Learn by Doing: A Model for Incorporating High-Impact Experiential Learning Into an Undergraduate Public Health Curriculum - Margaret L. Chorazy; Kimberly S. Klinedinst (Frontiers Media S.A., 2019)
Many accredited schools and programs of public health integrate experiential learning into the capstone experience for undergraduate public health majors; thus, the experiential learning capstone must be both cumulative and integrative. A goal of experiential learning is to foster the application of concepts and skills learned in the classroom to real-world public health situations. Students may benefit from earlier opportunities to engage in high-impact experiential learning activities. Therefore, the University of Iowa College of Public Health developed an experiential learning requirement that is separate from the capstone course. Our students' experiential learning activities do not need to be cumulative across the entire curriculum, but they should be integrative. Public health undergraduate students at the University of Iowa must successfully complete at least one of the following experiences in public health: research, internship, service learning, or global learning. This article will provide a model for the creation of an experiential learning program for undergraduate public health students that is separate from the culminating, capstone experience.